Interventional treatment and outcome in elderly patients with stable coronary artery disease - Rittger, Harald; Hochadel, Matthias; Behrens, Steffen; Hauptmann, K.E.; Zahn, Ralf; Mudra, H.; Brachmann, Johannes; Zeymer, Uwe (Herz, 2014)
The number of elderly and very elderly patients undergoing percutaneous coronary interventions (PCI) is increasing. We therefore analyzed data from the German ALKK registry (Arbeitsgemeinschaft Leitende Krankenhausärzte; Working Group of Hospital Cardiologists) to determine differences in procedural features, antithrombotic treatment, and in-hospital outcome in patients with coronary artery disease (CAD) according to age in a large series of patients.